2016
DOI: 10.1128/jvi.03113-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of HBZ and the Related APH-2 Protein Provides Insight into Human T-Cell Leukemia Virus Type 1 Pathogenesis

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) and type 2 (HTLV-2) are highly related retroviruses that transform T cells in vitro but have distinct pathological outcomes in vivo. HTLV-1 encodes a protein from the antisense strand of its proviral genome, the HTLV-1 basic leucine zipper factor (HBZ), which inhibits Tax-1-mediated viral transcription and promotes cell proliferation, a high proviral load, and persistence in vivo. In adult T-cell leukemia/lymphoma (ATL) cell lines and patient T cells, hbz is often th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 64 publications
3
50
1
2
Order By: Relevance
“…Human Immunodeficiency Virus (HIV) and Human T-cell Lymphotrophic Virus (HTLV) are the characterized retroviruses exhibiting this phenomenon. The proteins encoded by their antisense strands serve important functions, including control of viral sense transcription, as well as viral latency, pathology, and spread [14]. …”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Immunodeficiency Virus (HIV) and Human T-cell Lymphotrophic Virus (HTLV) are the characterized retroviruses exhibiting this phenomenon. The proteins encoded by their antisense strands serve important functions, including control of viral sense transcription, as well as viral latency, pathology, and spread [14]. …”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
“…HBZ also affects many other cellular processes, including host gene expression, innate immune signaling, apoptosis, autophagy, and DNA repair – all of which further influence the pathology of the HTLV-1 infection (reviewed in [3]). Similar to HTLV-1, HTLV-2, HTLV-3, and HTLV-4 are equally capable of producing antisense proteins – APH-2, APH-3, and APH-4, respectively – though their functions have not been clearly elucidated [4, 26, 2830]. …”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
“…Both HBZ and APH-2 counteract the activation of the NF-κB by Tax, but they differ in the mechanisms of inhibition [26,105]. Unlike APH-2, HBZ does not interact with Tax-1, whereas APH-2 does not drastically decrease p65 expression or induce its ubiquitination [119]. We demonstrated that HBZ and APH-2 also differ in their intracellular localization and that only APH-2 forms complexes with cytoplasmic host factors and Tax-2 [105].…”
Section: Deregulation Of Nf-κb Activation By Hbzmentioning
confidence: 82%
“…HBZ suppresses the transcription of various NF-κB target genes, including IL-8, IL2RA, IRF4, VCAM-1, CCND1, and VEGF [26,32,117,118]. The molecular mechanism of HBZ-mediated NF-κB inhibition has been investigated in several studies, which revealed that HBZ selectively suppresses the canonical NF-κB pathway by (i) interacting with p65 and reducing its DNA binding capacity, (ii) increasing the expression of PDLIM2, an E3 ubiquitin ligase that determines p65 degradation, and (iii) reducing p65 acetylation [117,119,120].…”
Section: Deregulation Of Nf-κb Activation By Hbzmentioning
confidence: 99%
“…In contrast, HBZ transcripts have been shown to be continuously present in HTLV-1-infected T cells (57)(58)(59)(60)(61)(62)(63)(64)(65). Therefore, given that both viral proteins have been reported to have relatively long half-lives (120)(121)(122), it is likely that HBZ and Tax are sometimes simultaneously present in primary HTLV-1-infected cells, during which time they could affect the repair of DSBs and additional processes involving DNA-PK.…”
Section: Discussionmentioning
confidence: 99%